Selection and evaluation of gene-edited knockout mutants of AtAAP2 and AtCRF4 homologs of rice for agronomic nitrogen use efficiency (ANUE) - Wakatabi, Kentaro; Selvaraj, Michael Gomez; Guzmán-Prada, Diego Alexander; Cuásquer, Juan Bosco; López-López, Karina; Endo, Masaki; Ishitani, Manabu (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2023)
Nitrogen (N) is essential for amino acid synthesis in rice production, but its excessive use poses an environmental concern. This research aimed to improve rice agronomic nitrogen use efficiency (ANUE) by knockout (KO) of rice homologs of the two selected genes from Arabidopsis thaliana: AtAAP2, an amino acid permease involved in N transportation in shoots, and AtCRF4, a transcription factor participating in N uptake in roots. The homologs of these genes in rice were identified based on amino acid sequence similarity and knocked out using CRISPR/Cas9 mediated gene editing (GE). The AAP2-KO and CRF4-KO lines were subjected to agronomic evaluations with three N doses: 100% (180 kg ha-1), 50% (90 kg ha-1), and 0% (0 kg ha-1) and showed a 130-175% increase in dry biomass weight and a 183-313% increase in panicle number compared to wild type (WT) in the first experiment. These lines also had slower leaf senescence, the so-called “stay-green” trait, indicating the KO effect of target genes in N metabolism. However, neither AAP2-KO nor CRF4-KO showed better yield or ANUE than WT. This study demonstrated the usefulness of GE technology in gene evaluation and highlighted the effects of AtAAP2 and AtCRF4 genes in the plant N cycle.